Thesaurus on Philippine literature - Sebastian, Romeo A. (Institute of Library Science, University of the Philippines Diliman, 1991)
aThe Thesaurus on Philippine Literature is a bilingual (English-Filipino) thesaurus. It is constructed to develop a standard and controlled vocabulary and to serve as a dictionary of descriptors in literature, specifically Philippine literature. The thesaurus can be used for indexing, storage and retrieval of information. The keywords were selected and collated from indexed articles, theses and dissertations, books, dictionaries and from the contributions of subject specialists. It is composed of 573 terms, 527 of which are keywords and 46 are non-preferred or approach terms. Out of the 527 keywords, 325 were given their equivalent or closest translation in Filipino. The rest were not translated either because some of the terms did not have any equivalent in the vernacular or the same was not applicable. Likewise it probably goes beyond its original meaning or primarily because of the nature of the term itself.